Peningkatan Keterampilan Menulis Teks Diskusi melalui Metode Diskusi The Power of Five Peserta Didik Kelas IX MTsN 4 Blitar - Sulistiani, Nanik - (Inovasi: Jurnal Diklat Keagamaan, 2023)
ABSTRACT The problem formulation of this scientific paper is whether The Power of Five discussion method can improve the discussion writing skills of class IX MTsN 4 Blitar students? How to improve the skills of writing discussion texts through the discussion method The Power of Five students of class IX MTsN 4 Blitar? The author hopes to be able to describe that The Power of Five discussion method can improve the discussion writing skills of class IX MTsN 4 Blitar students. The benefit that can be obtained from scientific writing for madrasas is the teacher's creativity in teaching which of course has an impact on maximum student learning outcomes. Creativity using teaching methods makes the learning atmosphere not monotonous. For teachers, teachers continue to carry out learning innovations. In addition to eliminating boredom because of the routine of teaching, it also contributes to the idea that teaching is not only transferring knowledge but conveying a humanitarian message through various teaching methods. The subject matter is important but what is more important is the method of delivering the material. There is evidence that the discussion method of The Power of Five can improve the discussion writing skills of class IX MTsN 4 Blitar students. Keywords: discussion text, the power of five, discussion method